The Impact of Switching Intention of Telelearning in COVID-19 Epidemic's Era: The Perspective of Push-Pull-Mooring Theory - Lin, Xin; Chien, Shih-Wen; Hung, Chung-Wen; Chen, Shih-Chih; Ruangkanjanases, Athapol (Frontiers in Psychology, 2021)
Under the impact of COVID-19, medical telelearning education is increasingly urgent to resolve the contradiction between medical students’ physical isolation and the need for on-site clinical teaching. In this study, push-pull-mooring theory (PPM) is integrated into a comprehensive model as a conceptual PPM framework: push factors (information system quality and perceived risk), pull factors (telepresence, trust, etc.), mooring factors (switching costs) and switching intention. The results show that most hypotheses were positive, but perceived risk did not influence user satisfaction significantly, and switching costs did not provide the impact on switching intention. This study provides a comprehensive empirical analysis of key factors influencing the choice of distance education by medical students through the integrated multi-model framework.